RECYCLING POLICY AND PROGRAM STRATEGIES FROM HOUSEHOLDS' PERSPECTIVES: A CASE STUDY IN MUAR ROYAL CITY - Moh, Yiing Chiee; Abd Manaf, Latifah (Malaysian Journal of Science, 2016)
This paper provides an introspective insight about households' expectations on recycling policy and program strategies at local community level via questionnaire survey conducted based on stratified random selection. Households strongly support strategies that provide them monetary benefit such as rebates (53.66%) and incentives (67.39%); convenience such as recycling drop-off centres (77.67%), recycling bins in housing areas (86.91%), and recycling collection points (84.18%); and knowledge gain such as environmental education on recycling (80.47%) and awareness campaign (81.45%). Based on the ranking, households prefer to be offered with recycling convenience and proper facilities, besides provided with knowledge, rather than purely receiving monetary rewards. It is unavoidable that there are individuals who are not susceptible to changes, especially when majority are most likely to make their own decision on whether to recycle. The success of recycling strategies depends on how these approaches are carried out to pave the way for households towards recycling behaviour. Positive results of households' contributions should be reported to quantify their effort into perspective. When majority starts to notice the trend, they would eventually start to recycle themselves. Based on the findings, this study discusses possible recommendations for implementations in the local municipalities to extend the potentials in achieving recycling community. Keywords: Household recycling; solid waste management; source separation; recycling strategies; recycling community